Occurrence and predictors factors for delirium in critically-ill older patients: a prospective cohort study - Rita Sofia Carneiro Martins (2021)
Purpose This study aims to analyze the occurrence of delirium in critically-ill older patients and to identify predictor factors for delirium. Methods This prospective study included critically-ill older patients admitted into level II units of Intensive Care Medicine Department of a University Hospital. Patients with Glasgow Coma Scale score ≤11, traumatic brain injury, terminal disease, history of psychosis, blindness/deafness or inability to understanding/speaking Portuguese were excluded. The Confusion Assessment Method-Short form (CAM-4) was used to delirium assessment. Results The final sample (n=105) had a median age of 80 years, being the majority female (56.2%), widowed (49.5%) and with complete primary education (53%). Through CAM-4, 36.2% of the patients had delirium. The delirium group presented more pre-existing cognitive decline (48.6% vs 19.6%, p=0.04) and severe dependency in instrumental activities of daily living (34.3% vs 14.8%, p=0.032), comparing to patients without delirium. The final multiple logistic regression model explained that patients with previous cognitive decline presented a higher risk for delirium (OR: 4.663, 95% CI: 1.055-20.599, p=0.042). Conclusion These findings corroborate previous studies, showing that cognitive decline is an independent predictor for delirium in older patients. This study is an important contribution for the knowledge regarding the predictor factors for delirium. The recognition of these factors will help to identify patients who are at high risk for this syndrome, and to implement an early screening and prevention strategies. However, further studies with larger samples, recruited from other clinical settings as well as analyzing other potential factors for delirium, will be needed.